Perfil epidemiológico y consecuencias de legrado uterino en pacientes que acuden al Área de Ginecología del Hospital General Isidro Ayora Loja - Chumbi Orellana, Luis Israel (2017)
Uterine curettage is a common problem in health services, so it is necessary that they have an epidemiological profile. The present study is of a cross-sectional type whose objective was to determine the epidemiological profile of uterine curettage and its consequences in patients who attend the Gynecology Area of the General Hospital Isidro Ayora Loja, January - June 2016, in a population of 1818 users, whose technique was the review of medical records. The results: 308 cases were found that had uterine curettage, which were included in the age group of 21-29 years 61%, civil union free 55%, secondary education 51%, rural residence 58%. Antecedents Gíneco-obstetrics 58% was diagnosed of childbirth. The main causes corresponded: incomplete abortion 46%, deferred abortion 22%. The most frequent consequences were: uterine bleeding 3.2%, uterine perforation 2% and infection 2%. A large number of patients (89.6%) did not present any type of consequences after performing uterine curettage. This problem is evident in the General Hospital Isidro Ayora Loja reason why the authorities and especially the health service should implement control measures. Keywords: epidemiological profile, uterine curettage, causes and consequences.